SCIENTIFIC ACHIEVEMENTS, ADVANCED EXPERIENCES IN COTTON VARIETIES AND COTTON FARMING (British Journal of Global Ecology and Sustainable Development, 2024)
This article describes the promising varieties of cotton grown in Uzbekistan and their biological properties, which have achieved high economic efficiency as a result. In addition, it provides extensive information about the best practices of farms and scientific achievements in cotton cultivation.